Pawang Ternalem Drama Text as a Material Indonesian Language in Grade VIII of Junior High School - Egitamersa Yolanda Br Bangun; Rosliani (Britain International for Academic Research (BIAR) Publisher, 2021)
This study aims to determine the intrinsic elements and the value of character education in the Pawang Ternalem drama script, as well as to determine the benefits of the analysis of drama scripts as teaching materials for Indonesian in Grade VIII. This study uses qualitative methods with data analysis techniques used are descriptive analysis. Based on the results of data processing, the research results show that in the Pawang Ternalem drama script there are intrinsic elements including themes, characters and characterizations, plot, setting, language style in dialogue, and mandate. In addition to the intrinsic elements of the drama script, 10 character education values were found, namely the values of religious character education, honesty, tolerance, hard work, creative, independent, respect for achievement, friendly / communicative, social care, and responsibility.